USE OF ANP IN DEVELOPING HAJORAN SALTED FISH BUSINESS PLAN TO IMPROVE COMPETITIVENESS - Siti Zubaida Sinaga; Darwis Harahap; Utari Evy Cahyani (JURNAL PROFIT, 2024)
This study aims to analyze the factors that affect the development of salted fish Micro Small Businesses in Hajoran Village , Pandan District, Central Tapanuli Regency, and formulate a development model using the Analytical Network Process (ANP) approach. This study uses a quantitative descriptive method with data collection techniques through observation, interviews, and questionnaires of 15 respondents consisting of Micro Small Business actors , community leaders, and related government agencies. The data is analyzed using Super Decisions software to determine the priority weight between factors and produce an effective and sustainable development strategy. The results of the study show that the main inhibiting factors for the development of salted fish Micro Small Businesses come from limited business capital (0.303), financial management (0.256), and availability of raw materials (0.249), while from external aspects include lack of partnerships (0.405), limited infrastructure (0.307), and lack of government policy support (0.279). The priority solutions produced through the ANP analysis are cooperation with financial institutions, strengthening collaboration between the government, the private sector, and the community, and building business networks and communities. The main strategy recommended is collaboration between local governments, academics, and the business world with the support of cooperatives as a capital and distribution booster. This ANP-based development model is expected to be a reference in empowering coastal Micro Small Businesses to improve the competitiveness and economic welfare of the community in a sustainable manner